2010
DOI: 10.1021/jm100602m
|View full text |Cite
|
Sign up to set email alerts
|

Development of Potent Glucagon-like Peptide-1 Agonists with High Enzyme Stability via Introduction of Multiple Lactam Bridges

Abstract: Glucagon-like peptide-1 (GLP-1) has the ability to lower the blood glucose level, and its regulatory functions make it an attractive therapeutic agent for the treatment of type 2 diabetes. However, its rapid degradation by enzymes like dipeptidyl peptidase-IV (DPP-IV) and neutral endopeptidase (NEP) 24.11 severely compromises its effective clinical use. Whereas specific DPP-IV inhibitors have been developed, NEP 24.11 targets multiple sites in the GLP-1 sequence, which makes it difficult to block. To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 67 publications
3
90
0
Order By: Relevance
“…Because the truncated peptide GIP(1-30) activates the GIP receptor as efficiently as the fulllength peptide GIP(1-42) (25), the GIP(1-30) was chosen as the peptide motif of our study. The peptide was functionalized with the chelator DOTA via 6-Ahx coupled to the side chains of Lys 16 and Lys 30 , respectively, to obtain EG1, EG2, and EG4. In EG4, the Met 14 was substituted with Nle, as a widely used strategy for stabilizing peptides against oxidative damage and allowing easier handling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the truncated peptide GIP(1-30) activates the GIP receptor as efficiently as the fulllength peptide GIP(1-42) (25), the GIP(1-30) was chosen as the peptide motif of our study. The peptide was functionalized with the chelator DOTA via 6-Ahx coupled to the side chains of Lys 16 and Lys 30 , respectively, to obtain EG1, EG2, and EG4. In EG4, the Met 14 was substituted with Nle, as a widely used strategy for stabilizing peptides against oxidative damage and allowing easier handling.…”
Section: Discussionmentioning
confidence: 99%
“…A new and promising family of G-proteincoupled receptors is the incretin receptor family (8,10,11). The imaging of tumors overexpressing the glucagonlike peptide 1 (GLP-1) receptor was proven to be successful in insulinoma preclinically (12)(13)(14)(15)(16)(17) and clinically (18,19). Recently, it was found that the second member of the incretin receptor family, the glucose-dependent insulinotropic polypeptide (GIP) receptor, is overexpressed in specific NETs.…”
mentioning
confidence: 99%
“…GLP-1 affects receptor binding and signaling (23)(24)(25)(26); however, to date there has been no investigation into the effect of C-terminal truncation of GLP-1 or Ex-4 on peptide helicity nor has there been research into the effect of inducing helicity in truncated analogs on receptor binding and signaling.…”
mentioning
confidence: 99%
“…21 Both techniques are known to stabilize and enhance native α-helicity, which may increase plasma stability and potentially enable in vivo dosing. Both approaches are also likely to increase proteolytic stability by shielding otherwise exposed scissile bonds from the relevant degrading enzymes.…”
mentioning
confidence: 99%